The Effectiveness of Learning Progression-based Biotechnology STEM Module to Improve Metacognitive Skills - Muninggar, Siti; Sarwanto; Ramli, Murni (LPPM Undiksha, 2023)
The times demand human resources that are proficient enough to face all situations and challenges confidently. These resources can be reflected in metacognitive skills. The existence of low metacognitive skills encourages the authors to use the learning progression-based biotechnology STEM module. The aim of this study is to analyze the effectiveness of the learning progression-based biotechnology STEM module to improve the metacognitive skills of the ninth-graders of junior high school in science subjects. This research is quasi-experimental research with a pretest-post-test control group design that tested the effectiveness of the module to improve the metacognitive skills of the ninth-graders of junior high school on biotechnology. The sampling technique used was simple random sampling which consisted of four ninth-grade classes. Each class consisted of 32 students. The four classes were grouped into two, namely the control group consisting of one class (32 students) and the experimental group consisting of three classes (96 students). The data were obtained by conducting tests analyze with an independent sample t-test. The results showed that the learning progression-based biotechnology STEM module had sufficient influence to improve the metacognitive skills of the ninth-graders of junior high schools.